2004
DOI: 10.1177/105382590402600307
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Theory, Research, and Evaluation in Adventure Education

Abstract: Some of the present approaches for studying adventure education are based on grounded theory, folk pedagogies, and existing social science theory. These approaches share some problems, including: (a) an overemphasis on outcomes without specifying processes, (b) a misunderstanding of how different types of evaluation contribute to theory, and (c) under-theorized evaluation and program models. As an alternative, program theory evaluation, which focuses on a “theory-program-outcome” model, in which all three comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 17 publications
1
29
0
Order By: Relevance
“…Further, such studies may consider a longer experi mental timeframe (e.g., a full academic year), particularly as this may afford greater opportunities for appropriate facilitation (Gass, 1993;Nadler & Luclaier, 1992) and allow examination of linkages between pro gram components and outcomes (Goldenberg, Klenosky, O'Leary, & Templin, 2000;Holman, Goldenberg, McAvoy, & Rynders, 2003). To conclude, though few significant differences emerged, this investigation has made a contribution in answer to the call for more empirical research (Baldwin et al, 2004;Hatch & McCarthy, 2005;Neill, 2003) into the potential psychological benefits derived from OAE participation.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Further, such studies may consider a longer experi mental timeframe (e.g., a full academic year), particularly as this may afford greater opportunities for appropriate facilitation (Gass, 1993;Nadler & Luclaier, 1992) and allow examination of linkages between pro gram components and outcomes (Goldenberg, Klenosky, O'Leary, & Templin, 2000;Holman, Goldenberg, McAvoy, & Rynders, 2003). To conclude, though few significant differences emerged, this investigation has made a contribution in answer to the call for more empirical research (Baldwin et al, 2004;Hatch & McCarthy, 2005;Neill, 2003) into the potential psychological benefits derived from OAE participation.…”
Section: Discussionmentioning
confidence: 88%
“…Such experiences as rock climbing, canoeing, orienteering, and camping have long been suggested to foster qualities such as initiative, perseverance, determination, self-restraint, cooperation, and resourcefulness (Celebi & Ozen, 2004;Luckner & Nadler, 1997;Schoel, Prouty, & Radcliffe, 1988). However, to date it has been noted (Baldwin, Persing, & Magnuson, 2004;Hatch & McCarthy, 2005) that claims of these activities' utility rely largely on anecdotal evi dence, because little empirical research has been conducted to examine their efficacy. This is somewhat surprising, especially given the espousal of outdoor adventure activities by those involved in, for example, cor porate development (Aubrey & McCleod, 1994), and the increased levels in outdoor adventure activities for the purpose of self-improvement (Anderson, Schleien, McAvoy, Lais, & Seligmann, 1997;Watts, Cohen, & Toplis, 1994).…”
Section: Michael Sheard and Jim Golbymentioning
confidence: 97%
“…Benard & Marshall, 2001a;Neill & Dias, 2001) have noted the growing demand for research assessing the effectiveness of adventure education on resilience enhancement as well as the applicability of the current resilience theories for diverse students and varying contexts (e.g., Ungar, 2005;Wasonga, Christman, Kilmer, 2003) as well as the influence of gender differences (Reimer, 2002;Sun & Stewart, 2007). Additionally, there is an increasing need for rigorous empirical evidence assessing adventure program outcomes as well as processes (Gass, 2007;Priest, 2001;Baldwin et al, 2004). Previous research on resilience enhancement has primarily taken place in school settings (e.g.…”
Section: Research Questionsmentioning
confidence: 99%
“…Benard and Marshall claimed that these external assets closely matched the research on resilience and what has been found to promote "successful development and learning" (p. 5). Analyzing the presence of these program components is an important step in further understanding adventure program theory and practice (Baldwin, Persing, & Magnuson, 2004).…”
mentioning
confidence: 99%
“…A large body of research identifies the positive outcomes of experiential education (EE) programs, such as Outward Bound and the National Outdoor Leadership School (e.g., Baldwin, Persing, & Magnuson, 2004;Hattie, Marsh, Neill, & Richards, 1997). Considerably less well understood is why these changes happen.…”
Section: Introductionmentioning
confidence: 99%